Earthquake Management And Mitigation At Pacitan Regency By Local Disaster Management Autority (Bpbd) Pacitan Regency Using Seiscomp3 Software - oktiyas muzaky Luthfi; Isna Putri Wulandari (Journal of Innovation and Applied Technology, 2018)
Pacitan is an area that is prone to earthquakes. Pacitan area in terms of the geological conditions of the area potentially affected by the threat of earthquakes, both centered in the sea (subduction zones) and on the ground in the form of active faults. The method used is the active participation and interviews. The process of detection as well as records of earthquakes assisted using Software SeisComP3. On display there SeisComP3 Indonesia map with symbols of the triangle which is the station that placed their vibration detectors of earthquakes throughout Indonesia. Based on the data of earthquakes during the last 6 months, have occurred 15 earthquakes in Pacitan and the surrounding area.